2021
DOI: 10.3390/en14238115
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Improvement in Pseudo-Plastic Material Using Ternary Hybrid Nanoparticles via Non-Fourier’s Law over Porous Heated Surface

Abstract: The numerical, analytical, theoretical and experimental study of thermal transport is an active field of research due to its enormous applications and use in numerous systems. This report covers the impacts of thermal transport on pseudo-plastic material past over a horizontal, heated and stretched porous sheet. Modeling of energy conservation is based upon a generalized heat flux model along with a heat generation/absorption factor. The modeled phenomenon is derived in the Cartesian coordinate system under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Their research revealed that as the bioconvection Lewis number increased, there was a corresponding decrease in the microorganism concentration profile. Algehyne et al, [24] conducted an analysis using the Buongiorno model to study mass and energy transmission in trihybrid nanofluids flow, without the inclusion of microorganisms. They concluded that trihybrid nanofluids demonstrated a remarkable enhancement in the rate of energy propagation when compared to simple and hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Their research revealed that as the bioconvection Lewis number increased, there was a corresponding decrease in the microorganism concentration profile. Algehyne et al, [24] conducted an analysis using the Buongiorno model to study mass and energy transmission in trihybrid nanofluids flow, without the inclusion of microorganisms. They concluded that trihybrid nanofluids demonstrated a remarkable enhancement in the rate of energy propagation when compared to simple and hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…They monitored the decline in velocity field by augmenting the values of slip parameter. Algehyne et al 9 studied the inclusion of ternary hybrid nanoparticles mixture in pseudo-plastic material past over a heated porous surface in the presence of heat generation and modified heat flux (Cattaneo–Christov model). They analyzed the shear thinning and thickening behavior of considered model for different values of power law index.…”
Section: Introductionmentioning
confidence: 99%
“…They implemented a numerical approach to obtain numerical results. Algehyne et al [11] investigated the effects of thermal transport on a pseudo-plastic material by heating and stretching a porous sheet. To stimulate energy conservation, heat generation and absorption are used.…”
mentioning
confidence: 99%